Case studies on Repcol and IORAM: Australian companies that are creating shareholder value through globally distributed work - Penter, Kevan; Pervan, Graham; Wreford, John (Indian Institute of Management, 2007)
The past decade has seen explosive growth in offshore Business Process Outsourcing (BPO) to India by US and European firms. However, Australian firms have been slower to take advantage of this trend. Offshore outsourcing by Australian firms is an under-researched area with little in the way of theory or models to guide management decisionmaking.The under-participation of Australian firms in Globally Distributed Work (GDW) to Indian service providers appears surprising given Australia?s full employment and aging population. Sixteen years of unbroken expansion of the Australian economy have created skills shortages that can be addressed by GDW, and Australia and India share many common characteristics that should facilitate mutually beneficial partnerships in GDW. Managers in Australian firms require a research-based framework to accelerate decision-making and adoption of Globally Distributed Work. The authors are endeavouring to use case studies to develop a decision-making framework that will assist Australian firms to make effective investments in GDW Repcol and Indian Ocean Rim Asset Management (IORAM) provide two examples of Australian firms that are creating value for shareholders through successful implementation of Globally Distributed Work. Repcol has leveraged GDW through a major investment in Bangalore. Effective management of GDW has enabled Repcol to grow from a small, privately owned Australian company into a global provider of financial services that is now listed on the Australian Stock Exchange. IORAM provides another example of an Australian boutique fund manager that is utilizing a?captive? Business Processing operation in Bangalore to drive higher returns from investment in listed Australiansmall capitalization stocks. Case studies of Repcol and IORAM provide insights for Australian mid-sized firms and organizations considering GDW. Both IORAM and Repcol appear to have utilized GDW in a manner that could be described as 'transformational'.